A c‐Myc‐MicroRNA functional feedback loop affects hepatocarcinogenesis12. Issue 6 (12th June 2013) - Han, Han; Sun, Dan; Li, Wenjuan; Shen, Hongxing; Zhu, Yahui; Li, Chen; Chen, Yuxing; Lu, Longfeng; Li, Wenhua; Zhang, Jinxiang; Tian, Yuan; Li, Youjun
Abstract c‐Myc (Myc) plays an important role in normal liver development and tumorigenesis. We show here that Myc is pathologically activated in and essential for promoting human hepatocellular carcinoma (HCC). Myc induces HCC through a novel, microRNA (miRNA)‐mediated feedback loop comprised of miR‐148a‐5p, miR‐363‐3p, and ubiquitin‐specific protease 28 (USP28). Myc directly binds to conserved regions in the promoters of the two miRNAs and represses their expression. miR‐148a‐5p directly targets and inhibits Myc, whereas miR‐363‐3p destabilizes Myc by directly targeting and inhibiting USP28. Inhibition of miR‐148a‐5p or miR‐363‐3p induces hepatocellular tumorigenesis by promoting G1 to S phase progression, whereas activation of them has the opposite effects. The Myc‐miRNA feedback loop is dysregulated in human HCC. Conclusion: These results define miR‐148a‐5p and miR‐363‐3p as negative regulators of Myc, thus revealing their heretofore unappreciated roles in hepatocarcinogenesis. (HEPATOLOGY 2013;57:2378–2389)